The Architect and the Emperor of Babylonia - Villard, Pierre (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Among the commonplaces associated to the last sovereign of the neo-Babylonian empire, Nabonid (556-539), the image of ‘king archaeologist’ had almost so much success as that of ‘mystic king’. And that ever since the publication of his inscriptions, among which several contain narratives of rediscovery and restoration of former temples, quite particularly the one who tells the reconstruction of Ebabbar, the sanctuary of Šamaš in Larsa, in the 10th year of his reign.